Curriculum Changes in the Visegrad Four: Three Decades After the Fall of Communism by Tomáš Janík, Štefan Porubský, Magdolna Chrappán, Kinga Kuszák - Gabriella Hegedűs (Debrecen University Press, 2021)
Bibliography of the reviewed book: Janík, T., Porubský, Š., Chrappán, M., & Kuszák, K. (2020). Curriculum changes in the Visegrad Four: three decades after the fall of communism. Waxmann.